2012
DOI: 10.1099/ijs.0.031088-0
|View full text |Cite
|
Sign up to set email alerts
|

Salinactinospora qingdaonensis gen. nov., sp. nov., a halophilic actinomycete isolated from a salt pond

Abstract: Salinactinospora qingdaonensis gen. nov., sp. nov., a halophilic actinomycete isolated from a salt pond A novel halophilic, filamentous, actinomycete strain, designated CXB832 T , was isolated from a salt pond in Qingdao, China. Optimal growth occurred at 37 6C, pH 7.0-8.0 and 9-12 % (w/v) NaCl. Strain CXB832 T formed pale yellow to deep yellow branched substrate mycelium without fragmentation. Abundant white aerial mycelium differentiated into long chains of spores and the spores were rod-shaped with smooth s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
7
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(8 citation statements)
references
References 38 publications
1
7
0
Order By: Relevance
“…The fatty acid profile contained iso-C 16 : 0 (54.14 %), C 16 : 0 (14.02 %), anteiso-C 17 : 0 (8.44 %), C 18 : 0 (5.42 %), C 18 : 1 ω7 c (5.15 %), iso-C 18 : 0 (4.17 %), 10-methyl C 18 : 0 (3.73 %), C 18 : 1 ω9 c (1.93 %), iso-C 17 : 0 (1.58 %) and anteiso-C 15 : 0 (1.41 %) (Table S1). The major components of the menaquinone, polar lipid and fatty acid profiles of Salinactinospora qingdaonensis CXB832 T were similar to those reported previously (Chang et al , 2012). The slight differences in the proportions of menaquinones and fatty acids and types of polar lipids may be due to the different experimental conditions used.…”
supporting
confidence: 87%
See 2 more Smart Citations
“…The fatty acid profile contained iso-C 16 : 0 (54.14 %), C 16 : 0 (14.02 %), anteiso-C 17 : 0 (8.44 %), C 18 : 0 (5.42 %), C 18 : 1 ω7 c (5.15 %), iso-C 18 : 0 (4.17 %), 10-methyl C 18 : 0 (3.73 %), C 18 : 1 ω9 c (1.93 %), iso-C 17 : 0 (1.58 %) and anteiso-C 15 : 0 (1.41 %) (Table S1). The major components of the menaquinone, polar lipid and fatty acid profiles of Salinactinospora qingdaonensis CXB832 T were similar to those reported previously (Chang et al , 2012). The slight differences in the proportions of menaquinones and fatty acids and types of polar lipids may be due to the different experimental conditions used.…”
supporting
confidence: 87%
“…The family Nocardiopsaceae , with Nocardiopsis as the type genus, was proposed by Rainey et al (1996) based on polyphasic analysis. At the time of preparing this manuscript, the family Nocardiopsaceae contained eight genera: Nocardiopsis (Meyer, 1976), Thermobifida (Zhang et al , 1998), Streptomonospora (Cui et al , 2001), Haloactinospora (Tang et al , 2008), Marinactinospora (Tian et al , 2009), Murinocardiopsis (Kämpfer et al , 2010), Spinactinospora (Chang et al , 2011) and Salinactinospora (Chang et al , 2012). As the largest genus in the family Nocardiopsaceae , Nocardiopsis contained 37 species and two subspecies (http://www.bacterio.net/nocardiopsis.html; Euzéby, 1997), more than half of which were isolated from saline environments such as salterns (Chun et al , 2000), saline or hypersaline soils (Al-Zarban et al , 2002; Li et al , 2003a, 2004, 2006; Hozzein et al , 2004; Zhang et al , 2008; Yang et al , 2008a; Chen et al , 2008, 2010; Hamedi et al , 2010, 2011) or marine samples (Sabry et al , 2004; Kroppenstedt & Evtushenko, 2006; Tian et al , 2009; Chen et al , 2009; Fang et al , 2011; Li et al , 2012).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…The isolates VA42-3 and VH47-3 form a separate cluster from close relatives of the genus Streptomyces (Figure 3 ). Interestingly, isolate VN6-2 exhibited 93.9% sequence similarity to Salinactinospora qingdaonensis CXB832 T , which was isolated from a salt pond in Qingdao, China (Chang et al, 2012 ). Phylogenetic analysis revealed that isolate VN6-2 forms a distinct branch together with an unpublished strain from marine sediment, actinomycete 095-35, which is well supported (Figure 3 ).…”
Section: Resultsmentioning
confidence: 99%
“…So far, there are nine genera of the family Nocardiopsaceae with validly published names: Nocardiopsis (Meyer, 1976), Thermobifida (Zhang et al , 1998), Streptomonospora (Cui et al , 2001), Haloactinospora (Tang et al , 2008), Marinactinospora (Tian et al , 2009), Murinocardiopsis (Kämpfer et al , 2010), Spinactinospora (Chang et al , 2011), Salinactinospora (Chang et al , 2012) and Allosalinactinospora (Guo et al , 2015). According to the statistics of Chang et al (2012), strains of the family Nocardiopsaceae were isolated from different environments, including hypersaline soils, marine sediments, compost, damp stored hay, manure heaps, a salt mine and salt lake. Recently, a novel strain, YIM 690008 T , was isolated from Daucus carota , a common vegetable collected from South Korea, which was found to be closely related phylogenetically to the genus Marinactinospora , but with very different phenotypic and chemotaxonomic characteristics.…”
mentioning
confidence: 99%